Influence of Self-Control on Hedonism and Consumptive Behavior in Generation Z Female SPayLater Users - Danisa Sabril Nurani; Era Agustina Yamini (IECON: International Economics and Business Conference, 2025)
Today, SPayLater market still  grow and increasingly popular among youth such as Generation Z. The study aim to test the effect of setlf-control on hedonic lifestyle and consumptive behavior. The research used a quantitative method by conducting a survey with a questionnaire distributed directly to respondents, there were 300 respontents chosen using the purposive sampling tehcnique. The data in the study were analyzed using the SPSS 25 software. The results showed that (1) self-control had a significant negative effect on hedonic lifestyle, (2) self-control had a significant negative effect on consumptive behavior, (3) hedonic lifestyle had a significant positive effect on consumptive behavior. Based on the result of the study, it can be concluded that the higher a person’s self-control, the lower their hedonic lifestyle and consumptive behavior and vice versa. Then, the higher hedonic lifestyle, the higher the consumptive behavior.